2015
DOI: 10.1111/ddi.12369
|View full text |Cite
|
Sign up to set email alerts
|

Historic and prehistoric human-driven extinctions have reshaped global mammal diversity patterns

Abstract: Aim To assess the extent to which humans have reshaped Earth's biodiversity, by estimating natural ranges of all late Quaternary mammalian species, and to compare diversity patterns based on these with diversity patterns based on current distributions. Location Globally. Methods We estimated species, functional and phylogenetic diversity patterns based on natural ranges of all mammalian species (n = 5747 species) as they could have been today in the complete absence of human influence through time. Following t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
250
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(263 citation statements)
references
References 65 publications
11
250
0
2
Order By: Relevance
“…In contrast, our results are consistent with previous intercontinental comparisons of small mammal assemblages in desert regions, in which small mammal communities also showed a high heterogeneity of species and traits within and among continents [59,60]. The current patterns of beta diversity are undoubtedly impacted by humans since their emergence, through extinctions and range contractions [63]. Therefore, the historical patterns of convergence or radiation between and among realms and biomes might also have been obscured.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, our results are consistent with previous intercontinental comparisons of small mammal assemblages in desert regions, in which small mammal communities also showed a high heterogeneity of species and traits within and among continents [59,60]. The current patterns of beta diversity are undoubtedly impacted by humans since their emergence, through extinctions and range contractions [63]. Therefore, the historical patterns of convergence or radiation between and among realms and biomes might also have been obscured.…”
Section: Discussionsupporting
confidence: 90%
“…(Valdiosera et al, 2007). This is also in agreement with a general trend of mountainous areas being less vulnerable to anthropogenic impacts (Faurby & Svenning, 2015). B.P.…”
Section: Discussionsupporting
confidence: 88%
“…Li et al (2002) provide evidence that Rhinopithecus was first extirpated from lower elevation during the last 400 years. Higher elevation areas are more remote and difficult for humans to access and utilize and other studies have found less deforestation, more reforestation and afforestation, less range contraction, and less extinction in topographically steep areas (Laliberte and Ripple 2004; Fisher 2011; Sandel and Svenning 2013; Faurby and Svenning 2015; Nüchel and Svenning 2017). Furthermore, many other species in the region, e.g., giant panda ( Ailuropoda melanoleuca ) and red panda ( Ailurus fulgens ), have also been impacted by strong anthropogenic pressure during the recent centuries with population declines and range retractions as consequences (Ceballos and Ehrlich 2002; Zhu et al 2010; Hu et al 2011).…”
Section: Discussionmentioning
confidence: 98%